Step by step pediatric echocardiography - Gera, Rani (Japee Brothers Medical Publishers, 2010)
This concise step-by-step guide and the accompanying CD-ROM provide those just beginning to work in the echo lab with the basic information concerning the diagnostic interpretation of the echocardiograph.